Cervicogenic headache Part 1: An anatomic and clinical overview (awarded the OPTP Award for Excellence in a Published review of the Literature ** ) - Kathryn L. Smith; Claire Horn (AOSIS, 1998)
Cervicogenic headache is a headache arising from painful dysfunction of the upper cervical spine. This paper reviews current literature on the anatomy, etiology, clinical presentation and differential diagnosis of cervicogenic headache. Lower cervical spine levels and cervical soft tissue components will be incorporated where they have a direct influence on the upper three segments.